Pengembangan Potensi Ekowisata Sungai Pekalen Atas, Desa Ranu Gedang, Kecamatan Tiris, Kabupaten Probolinggo - Afifah Nur Aulia; Luchman Hakim (Department of Urban and Regional Planning, Diponegoro University, 2017)
River ecosystem is a potential resource for ecotourism development necessary to job creation for the local community and river conservation support. The aims of this research are to depict the ecotourism attraction potentials, to prepare ecotourism product designs, to evaluate tourist’s preferences regarding ecotourism objects and attractions, and to develop a typology of tourism products prospectively developed along the Pekalen Atas River. This study was completed from October 2016 to March 2017 in Pekalen Atas River, Ranu Gedang Village, Tiris Subdistrict, Probolinggo Regency. This research covered object identification and mapping steps along the riverbank, and then followed by respondent preferences testing toward the ecotourism objects required to the making of ecotourism product development’s classification and ranking. This product was also developed by taking stakeholders’ feedback into account during the Focus Group Discussion (FGD). The result reveals that the Pekalen Atas Riverbank consists of 26 rapids, three waterfalls, three fields, three caves and 11 animal species. The potential objects could be classified into rafting and non-rafting. Based on tourists’ perceptions, the non-rafting objects are considered “attractive” so that their further developments should meet the principles of sustainable natural resources utilization compliance. The FGD results confirmed three types of ecotourism products that could be developed along the Pekalen Atas Riverbank, i.e. low-, medium-and hard-level product.